2006
DOI: 10.2174/092986706779010324
|View full text |Cite
|
Sign up to set email alerts
|

Statin Therapy-Evidence Beyond Lipid Lowering Contributing to Plaque Stability

Abstract: Primarily statin drugs inhibit hepatic 3-hydroxy 3-methylglutaryl coenzyme A (HMG-CoA) reductase, which is responsible for the reduction in circulating low-density lipoprotein (LDL) cholesterol. Several findings from recent research studies indicate that statins have multiple actions that favorably influence key factors involved in the atherogenic process. These so-called pleiotropic properties affect various aspects of cell function, inflammation, coagulation, and vasomotor activity. These effects are mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
1
27
0
2
Order By: Relevance
“…In this study, statins showed LDL-cholesterol lowering effects; however, considering the impact of other multiple pleiotropic effects caused by statins, such as effects on endothelial function, inflammation, arterial myocyte proliferation, migration and apoptosis, plaque stability, platelet activity, and the coagulation process, the lowering of LDL-cholesterol is not the only relevant parameter for the achievement of successful risk reduction. 11,35 As in other studies, LDL-cholesterol levels did not show a significant effect on any endpoint. Results of various studies suggest that treatment with statins should be indicated in accordance with the global vascular risk profile and not primarily on base-level LDLcholesterol concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, statins showed LDL-cholesterol lowering effects; however, considering the impact of other multiple pleiotropic effects caused by statins, such as effects on endothelial function, inflammation, arterial myocyte proliferation, migration and apoptosis, plaque stability, platelet activity, and the coagulation process, the lowering of LDL-cholesterol is not the only relevant parameter for the achievement of successful risk reduction. 11,35 As in other studies, LDL-cholesterol levels did not show a significant effect on any endpoint. Results of various studies suggest that treatment with statins should be indicated in accordance with the global vascular risk profile and not primarily on base-level LDLcholesterol concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…5,6,8,9 Collectively, these actions are known as the pleiotropic effects of statins. These unexpected beneficial actions seen with HMG-CoA reductase inhibitors result from improved endothelial function, less oxidized LDL uptake by endothelial cells and macrophages, increased nitric oxide synthase expression, decreased migration of monocytes and differentiation into activated macrophages, and less overall inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Here probably, a combination of PPAR ligands and naturally occurring ligands like 24(S), 25-epoxycholesterol may work better, but again this need to be tested. Treatment of macrophages with the PPARg ligands troglitazone and pioglitazone upregulated the expression of the SREBP-2 target genes HMG-CoA synthase and HMG-CoA reductase [202][203][204][205] ; however, in HepG2 and Caco-2 cells PPARg activation by troglitazone lowers the cholesterol synthesis by reducing the concentration of nuclear SREBP-2 and successive downregulation of its target genes involved in cholesterol synthesis. 206 These results indicate that PPARg and SREBP-2 interaction and regulation may be tissue/cell-specific which makes the targeting of this pathway more challenging.…”
Section: Macrophages As Therapeutic Target Of Atherosclerosis * 493mentioning
confidence: 98%